Library Digitalization Through the Provision of Facilities of Sekolah Indonesia Kuala Lumpur (SIKL)’S Library - Hasyim, Sirojuzilam; Irsad; Syafii, Muhammad; Sukardi; Rahman, Arif (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The international community service activities carried out at the Sekolah Indonesia KualaLumpur aim to provide real benefits in the effort to create a digital library at SIKL which can increase interest in learning in children attending the Kuala Lumpur Indonesian School, Malaysia and as a learning medium that is more accessible and fun that in the future can create quality human resources and be able to compete in the era to come. KualaLumpur Indonesian School, Malaysia in the end with the international dedication carried out by the Postgraduate Lecturer in Economics through the program "Library Digitization Through Provision of Sekolah Indonesia KualaLumpurLibrary Facilities" can support facilities for digital libraries at SIKL. Library facilities at SIKL are still limited. With the existing conditions, it is necessary to have media that can be used to make it easier to find information and broader knowledge that can increase interest in learning SIKL students. These facilities are in the form of a PC, TV, and speakers. The results of this service are expected to contribute to increasing interest in learning and facilitating the learning process at the Indonesian School of Kuala Lumpur, Malaysia.